2010
DOI: 10.2165/11530300-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Serious Adverse Reactions to Cholinesterase Inhibitors

Abstract: An increased risk of SADRs related to cholinesterase inhibitors was associated with the use of antipsychotics (with no difference between conventional and atypical antipsychotics), drugs targeting the alimentary tract/metabolism and antihypertensive drugs. It was not associated with the use of other psychotropic drugs, other non-psychotropic CNS drugs or with the use of antiarrhythmic agents. The association with drugs targeting the alimentary tract and metabolism could result from a protopathic bias or reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In patients with impaired cognition, the reduction of adherence, polymedication and the increased sensitivity to drugs with anticholinergic properties could be risk factors for adverse drug reactions (ADRs. ) While ADR related to cholinesterase inhibitors (ChEI) or drug‐induced cognitive impairment are often studied and well described, few studies have evaluated the relationship between dementia and ADR occurrence …”
Section: Introductionmentioning
confidence: 99%
“…In patients with impaired cognition, the reduction of adherence, polymedication and the increased sensitivity to drugs with anticholinergic properties could be risk factors for adverse drug reactions (ADRs. ) While ADR related to cholinesterase inhibitors (ChEI) or drug‐induced cognitive impairment are often studied and well described, few studies have evaluated the relationship between dementia and ADR occurrence …”
Section: Introductionmentioning
confidence: 99%
“…Grossberg et al 46 found no significant interaction between rivastigmine and antihypertensive medication as a group in their cohort study but when analysed separately, the use of diuretics and rivastigmine was related to a significantly higher rate of serious adverse events while centrally acting antihypertensives, ACE inhibitors and calcium channel blockers were not. Furthermore, the results of two database studies showed that use of antihypertensive treatment was significantly associated with serious adverse drug reactions in patients treated with cholinesterase inhibitors 47 and beta blockers were among the most frequently encountered drugs involved in drug-drug interactions with cholinesterase inhibitors 48 .…”
Section: Use Of Cholinesterase Inhibitorsmentioning
confidence: 99%
“…70,76,77 Elderly people and those under treatment with conventional or atypical antipsychotics are more likely to develop severe adverse effects. 78 In many pathological states of the nervous system, excitotoxicity promotes functional and structural damage. This is why experiments have shown that memantine has neuroprotective effects in patients with cerebral ischaemia, intraparenchymal cerebral haemorrhage, HIV-associated dementia, head trauma, carbamate insecticide poisoning, glaucoma, motor neuron diseases, Huntington disease, Parkinson's disease, and AD.…”
Section: Should Cholinesterase-inhibitor Treatment Be Tested In Patiementioning
confidence: 99%